Residential energy efficiency: Benefits of minimum energy performance standard (MEPS) implementation for television in Malaysia - Isa A.M.; Roslan M.E.M.; Salleh S.F. (Science Publishing Corporation Inc, 2023)
A popular strategy for promoting energy efficiency at the national level is through the minimum energy performance standards (MEPS). Malaysia implemented MEPS in 2013 for five common household appliances; air conditioners, refrigerators, fans, televisions, and lamps. These products must undergo a performance test. Only products that meet the minimum standards are allowed to enter the Malaysian market. Based on their performance, ratings are awarded ranging from 2-star up to 5-star. A survey the authors conducted in 2017 found that about 98% of televisions sold in Malaysia have already achieved 5-star rating. This paper explores the implications of this finding and quantifies the possible savings that can be achieved in terms of electricity savings and emission reductions. 2018 Authors.